HUMAN RESOURCES (HR) DEVELOPMENT AT THE EMPLOYEE LEVEL ETHOS - Rusmasari Marisya; Septin Maisharah K; Irwan Sugiarto (SEAN Institute, 2023)
The purpose of this research is to identify the description of Human Resource Development at the level of Employee Work Ethics at the Hotel Hilton Bandung. Employees at the Hotel Hilton Bandung, which has a population of 52 people, provided the data. The sample methodology used is saturation sampling, which means sampling based on the existing population. The research method used in this study is associative research. Based on research conducted by evaluating the data gathered there is a relationship between Human Resource Development Factors and a positive and significant influence on Employee Work Ethics at Hilton Bandung Hotel with a value of 3.962, while t table is 2.006, so the t value is 3.962> 2.006. The coefficient of determination results